Pathological characteristics analysis of children with intermittent and persistent hydronephrosis due to uretero-pelvic junction obstruction - Yan, Ma; Jizhen, Zou; Ping, Xiao; Cheng, Huang; Dongsheng, Bai (Frontiers in Pediatrics, 2024)
To analyze from a pathological perspective the differences between intermittent and persistent hydronephrosis in children with uretero-pelvic junction obstruction.Methods: 23 children who underwent unilateral dismembered pyeloplasty(Anderson -Hynes operation) for intermittent hydronephrosis from September 2017 to March 2024 were included in the observation group. They were compared with a control group consisting of 23 children with persistent hydronephrosis matched for age, gender, and affected side. All children had the narrowed segment surgically excised during the operation, while other obstructive causes (such as polyps, crossing vessels, or tumor compression) were excluded. The specimens were analyzed for muscle and collagen content using Masson 's trichrome staining, and the collagen-to-muscle ratio (CMR) was calculated. The number of Cajal-like cells was quantified with c-kit immunohistochemical staining. For all slides, 10 random fields of view were selected under a 400x optical microscope to record pathological data and calculate mean values. Pathological indicators between the two groups were compared using the T-test and the Chi-square test, with P < 0.05 considered statistically significant.The observation group showed a significant difference in the number of fields with low, medium, and high densities of Cajal-like cells compared to the control group 132 (57.4%) vs. 173 (75.2%); 70 (30.4%) vs. 38 (16.5%); 28(12.2%) vs. 19 (8.3%), P < 0.001. The uretero-pelvic junction in children with intermittent hydronephrosis had lower collagen content, higher muscle content, and a more regular arrangement. The collagen -muscle ratio was significantly lower than that in children with persistent hydronephrosis (1.59 ±0.65) vs. (3.98±1.19), P < 0.001. Conclusion: Compared with persistent hydronephrosis, the narrowed segment at the ureteropelvic junction in children with intermittent hydronephrosis has a higher density of Cajal -like cells; lower collagen content, and higher muscle content (lower collagen -muscle ratio).